Interconnection of VSC‐HVDC and LCC‐HVDC using DC–DC autotransformer. Issue 18 (27th June 2019) - Yang, Zhihan; Li, Mengbo; Lu, Xiaojun; Xiang, Wang; Zuo, Wenping; Yao, Liangzhong; Lin, Weixing; Wen, Jinyu
Abstract : This article investigates the feasibility of interconnecting LCC‐HVDC and VSC‐HVDC through an un‐interrupted DC autotransformer (DC AUTO). The interconnected system aims at taking advantage of two HVDC technologies. To begin with, the system configuration and the potential benefits are illustrated. Then, the corresponding control strategies towards LCC‐HVDC, VSC‐HVDC, and the un‐interrupted DC AUTO are proposed. The installed controllers enable the system stable operation during both normal time and faulted conditions. Finally, a four‐terminal test system is built on PSCAD/EMTDC platform to validate the technical feasibility of the interconnected system and the effectiveness of the proposed control strategy.